Concomitant preoperative airflow obstruction confers worse prognosis after trans-thoracic surgery for esophageal cancer - Lang, Ke; Wang, Xiaocen; Wei, Tingting; Gu, Zhaolin; Song, Yansha; Yang, Dong; Wang, Hao (Frontiers in Surgery, 2023)
Background: Airflow obstruction is a critical element of chronic airway diseases. This study aimed to evaluate the impact of preoperative airflow obstruction on the prognosis of patients following surgery for esophageal carcinoma. Methods: A total of 821 esophageal cancer patients were included and classified into two groups based on whether or not they had preoperative airflow obstruction. Airflow obstruction was defined as a forced expiration volume in the first second (FEV1)/forced vital capacity (FVC) ratio below the lower limit of normal (LLN). A retrospective analysis of the impact of airflow obstruction on the survival of patients with esophageal carcinoma undergoing esophagectomy was performed. Results: Patients with airflow obstruction(102/821, 12.4%) had lower three-year overall (42/102, 58.8%) and progression-free survival rate(47/102, 53.9%) than those without airflow obstruction(P<0.001). Multivariate analyses showed that airflow obstruction was an independent risk factor for overall survival(Hazard Ratio= 1.66; 95%CI: 1.17-2.35, P=0.004) and disease progression(Hazard Ratio= 1.51; 95%CI: 1.1-2.08; P=0.01). A subgroup analysis revealed that the above results were more significant in male patients, BMI<23kg/m2 patients or late-stage cancer(stage III-IVA) (P=0.001) patients and those undergoing open esophagectomy(P<0.001). Conclusion: Preoperative airflow obstruction defined by FEV1/FVC ratio below LLN was an independent risk factor for mortality in esophageal cancer patients after trans-thoracic esophagectomy. Comprehensive management of airflow obstruction and more personalized surgical decision-making are necessary to improve survival outcomes in esophageal cancer patients.